ANALYSIS OF FAILURE DETECTION AND VISIBILITY CRITERIA IN PANTOGRAPH-CATENARY INTERACTION - Parlakyildiz, Sakir; Gencoglu, Muhsin Tunay; Cengiz, Mehmet Sait (Znack Publishing House, 2020)
The main purpose of new studies investigating pantograph catenary interaction in electric rail systems is to detect malfunctions. In the pantograph catenary interaction studies, cameras with non-contact error detection methods are used extensively in the literature. However, none of these studies analyse lighting conditions that improve visual function for cameras. The main subject of this study is to increase the visibility of cameras used in railway systems. In this context, adequate illuminance of the test environment is one of the most important parameters that affect the failure detection success. With optimal lighting, the rate of fault detection increases. For this purpose, a camera, and a LED luminaire 18 W was placed on a wagon, one of the electric rail system elements. This study considered CIE140-2019 (2nd edition) standards. Thanks to the lighting made, it is easier for cameras to detect faults in the electric trains on the move. As a result, in scientific studies, especially in rail systems, the lighting of mobile test environments, such as pantograph-catenary, should be optimal. In environments where visibility conditions improve, the rate of fault detection increases.
Keywords: rail system lighting; pantograph-catenary interaction; fault detection visibility; luminance; illuminance